Penerapan Strategi Metakognitif untuk Meningkatkan Kemampuan Menalar tentang Lama Waktu Suatu Kejadian - Ismini Ismini (Journal on Education, 2021)
The purpose of this study was to determine whether or not there was an increase in mathematical reasoning ability by applying metacognitive strategies to 3rd grade students of SD Negeri Airlangga I/198 Surabaya and to find out how much increased mathematical reasoning ability by applying metacognitive strategies to 3rd grade students of SD Negeri Airlangga I/ 198 Surabaya City. Reasoning is one of the goals of mathematics. To improve these abilities, of course, it cannot be separated from learning efforts in schools. Although learning in schools so far has a high role in student activity, for example through the formation of study groups, it turns out that the impact on students' reasoning abilities has not been seen. Therefore, the author as a teacher in the class tries to implement the concept of learning in the 2013 curriculum which focuses on student learning activities to get educational values ​​through metacognitive strategies. This method is expected to be able to improve the Reasoning Ability of the Length of Time of an Event in 3rd grade students of SD Negeri Airlangga I/198 Surabaya City. The research was conducted with a two-cycle action mechanism. And based on the results of data analysis, it can be concluded that there is an increase in mathematical reasoning ability by applying metacognitive strategies to 3rd grade students of SD Negeri Airlangga I/198, Surabaya City. The increase in mathematical reasoning ability by applying metacognitive strategies to 3rd grade students of SD Negeri Airlangga I/198 Surabaya City by 22%.